SOCIOLINGUISTIC AND HISTORICAL CHARACTERISTICS OF ARABIC BORROWINGS IN MODERN FRENCH - Лаухіна, Інна (Modern engineering and innovative technologies, 2022)
The relevance of scientific research is determined by the small number of studies on Arabic-French language contacts, as well as incomplete coverage of the problem of adaptation of Arabic borrowings in a lexical fund of modern French. The historical preco